1986
DOI: 10.1029/jd091id04p05205
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic model studies of atmospheric droplet chemistry: 2. Homogeneous transition metal chemistry in raindrops

Abstract: Considerable evidence indicates that dissolved transition metal ions (TMI) are capable of catalyzing oxidations in atmospheric water droplets, at least in certain circumstances. Wide variations in the importance of TMI chemistry are expected in these systems because concentrations of transition metals in water droplets range over at least 4 orders of magnitude. In the present work we perform an extensive series of model calculations for TMI chemistry in raindrops. The specific TMI discussed are iron, manganese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(85 citation statements)
references
References 99 publications
1
83
0
1
Order By: Relevance
“…In terms of relative contribution to total European emissions for different pollutants, NMVOC from forests and vegetation are clearly the most important emission sources (Simpson et al, 1998). Several thousand different biogenic non-methane volatile organic compounds (NMVOCs) have been identified (e.g., Isidorov et al, 1985;Graedel et al, 1986;Puxbaum, 1997;Fall, 1999). Plants are the largest biogenic sources of nonmethane volatile organic compounds.…”
Section: Modeling Of Biogenic Sourcesmentioning
confidence: 99%
“…In terms of relative contribution to total European emissions for different pollutants, NMVOC from forests and vegetation are clearly the most important emission sources (Simpson et al, 1998). Several thousand different biogenic non-methane volatile organic compounds (NMVOCs) have been identified (e.g., Isidorov et al, 1985;Graedel et al, 1986;Puxbaum, 1997;Fall, 1999). Plants are the largest biogenic sources of nonmethane volatile organic compounds.…”
Section: Modeling Of Biogenic Sourcesmentioning
confidence: 99%
“…The soluble Fe(III) may then be photoreduced to Fe(II). Graedel et al (1986), Weschler et al (1986), and Faust and Hoigne (1990) suggested that at a pH of -2.5-5, typical of cloud and rain droplets, the following reaction may produce Fe(II): hv [Fe(OH) (H20)J2+ H20 -+…”
Section: A Final Region Is the High Latitude Southernmentioning
confidence: 99%
“…The major effects of transition metals are principally linked to the homogeneous aqueous phase chemistry. Graedel et al (1986) first attempted to explain the complex redox chemistry of transition metals in atmospheric water through the development of a detailed kinetic model. Their results indicated that transition metals (Cu(I) and Cu(II), Fe(II) and Fe(III) and Mn(II) and Mn(III)) could play an important role in the radical chemistry of the atmospheric water phases.…”
Section: Introductionmentioning
confidence: 99%